Disruptive behavior in university quarters - a field study on a sample of students - ghiboub, hakim; mesaad, fatehallah (Journal of Social Sciences and Humanities, 2024)
This study aims to find out the reason for the existence of property sabotage in university residences, which has become a phenomenon that cannot be ignored, especially when the behavior occurs from the educated class. Which is reflected on public property as a result of some hostile behavior in destroying these properties as an expression of a specific reality or in order to deliver a specific message or impose the logic of the group to which he belongs.